Hate Speech Youtuber MK: A Forensic Linguistics Study - Mirsa Umiyati; Ni Putu Meira Purnama Yanti (Universitas Warmadewa, 2021)
Hate speech refers to speech that contains hate that is intended to cause certain impacts, either directly or indirectly. As the digital era develops, hate speech is now a very easy thing to happen. Hate speech can be done either individually or in certain groups which certainly causes polemics and problems in the community. One of them is Muhamad Kace (MK), a Youtuber from West Java who is famous for his vulgarity in pouring his content. Therefore, this study aims to analyze the form and meaning of several MK utterances that contain ethnicity, religion, race, and class elements of hate speech. The source of the data in this study was the direct speech uploaded to YouTube on August 20th, 2021. The data was obtained by observing the method with a note-taking technique, then the data was analyzed descriptively qualitatively. The element of ethnicity, religion, race, and class in the hate speech is proven semantically and pragmatically using the theories by Chaer (2013) and Yule (2006). The results of the analysis showed that the utterances of Youtuber MK were full of insulting and degrading words which were clearly seen from the lexical meaning, grammatical meaning, expressive illocutionary speech acts, and directive illocutionary speech acts.